2019
DOI: 10.2217/fon-2018-0654
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes In Patients With Metastatic Bladder Cancer In The Usa: A Retrospective Electronic Medical Record Study

Abstract: Aim: Investigate the effectiveness of chemotherapy for first-line (1L) treatment of metastatic bladder cancer (mBC). Methods: Retrospective cohort study evaluating treatment patterns/outcomes in 1155 mBC patients receiving initial treatment in the community practice setting from January 2010 to June 2014, and followed through July 2016. Results: The most commonly utilized 1L and second-line (2L) regimens were platinum-based and taxane-based, respectively. Median (95% CI) OS for all patients from 1L initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
0
28
0
3
Order By: Relevance
“…Although this is a significant modeling assumption, the results align well to clinical practice e a retrospective observational study reports a median treatment duration for carboplatin plus gemcitabine of 2.6 months, closely matching the modeled median treatment duration of 2.8 months in our analysis. 23 This study has several limitations. The analysis did not include patients who were ineligible for any platinum-containing chemotherapy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although this is a significant modeling assumption, the results align well to clinical practice e a retrospective observational study reports a median treatment duration for carboplatin plus gemcitabine of 2.6 months, closely matching the modeled median treatment duration of 2.8 months in our analysis. 23 This study has several limitations. The analysis did not include patients who were ineligible for any platinum-containing chemotherapy.…”
Section: Discussionmentioning
confidence: 92%
“…The predicted median OS is 7.4 months, falling in the range of reported values from the 4 studies (range, 7.2-10 months), [19][20][21][22] and between the values seen in real world studies for US patients not treated with cisplatin (range, 6.9-9.5 months). 4,23 Further comparison of PFS and OS between studies and the model results is shown in Supplemental Table 4 (in the online version).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the use of chemotherapy, Galsky's criteria are widely used to identify patients eligible or ineligible for cisplatin-based chemotherapy, although there are other factors that are affecting the physician's decision as reported in large retrospective studies from daily practice [8,24]. In IMvigor 130 trial, patients were stratified according to classical Galsky's criteria, but investigators were able to choose between cisplatin + gemcitabine or carboplatin + gemcitabine according to their own standard practice and regardless of Galsky's status.…”
Section: Challenges After Imvigor130 Results To Face With the Combinamentioning
confidence: 99%
“…Moreover, patients with poor Bajorin risk factors, ie, Eastern Cooperative Oncology Group performance status (ECOG PS) ≥ 2 and/or visceral metastases, have a worse prognosis [7,8]. Patients with locally advanced or metastatic UC (generally termed advanced UC) represent a relatively frail population; US real-world studies show that patients receiving firstline (1L) therapy tend to be elderly (median age, 71-77 years), have compromised PS (ECOG PS ≥ 1 in 58-86% and ≥ 2 in 13-19%), and have a high prevalence of renal impairment (creatinine clearance [CrCl] < 60 mL/min in 49%) [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%